2016
DOI: 10.1002/elps.201500561
|View full text |Cite
|
Sign up to set email alerts
|

LC‐MS/MS analysis of permethylated free oligosaccharides and N‐glycans derived from human, bovine, and goat milk samples

Abstract: Oligosaccharides in milk not only provide nutrition to the infants, but also have significant immune biofunctions such as inhibition of pathogen binding to the host cell. The main component in milk oligosaccharides is free oligosaccharides. Since the proteins in milk are highly glycosylated, N-glycans in milk also play an import role. In this study, we investigated the permethylated free oligosaccharides and N-glycans extracted from bovine, goat and human milk using LC-MS/MS. Quantitation profiles of free olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 55 publications
2
95
0
Order By: Relevance
“…With the help of an established separation technique for permethylated glycans coupled with optimized CID and an HCD MS/MS method, we are able to distinguish between glycan isomers by tandem MS. The described approach enabled the identification of fucose and galactose site isomers as well as galactose linkage isomers and expands upon our previous studies (26, 27, 72) by extending the diversity of isomeric structures characterized by tandem MS to include complex glycans from model glycoproteins as well as human serum.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…With the help of an established separation technique for permethylated glycans coupled with optimized CID and an HCD MS/MS method, we are able to distinguish between glycan isomers by tandem MS. The described approach enabled the identification of fucose and galactose site isomers as well as galactose linkage isomers and expands upon our previous studies (26, 27, 72) by extending the diversity of isomeric structures characterized by tandem MS to include complex glycans from model glycoproteins as well as human serum.…”
Section: Introductionmentioning
confidence: 68%
“…Isomeric separation of permethylated glycans using PGC-LC-MS/MS at room temperature was first reported by Costello and co-workers (65). Here we employ a strategy that builds upon previous studies where porous graphitic carbon (PGC) was applied for the separation of native alditols (6671) in addition to our own work where an optimized high temperature PGC-LC method was implemented for the isomeric separation of permethylated glycans in human bovine and milk samples (26, 72). Both monosaccharide site isomers and linkage isomers can be baseline resolved in this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The fragment ion at m/ z 468.36 is a diagnostic ion for all core fucosylated glycans. 21 Confident assignment of the fucosylation sites was made possible because of the absence of fucose migration, which is eliminated by permethylation.…”
Section: Resultsmentioning
confidence: 99%
“…This separation is thus based on the properties of the glycan and results in the smallest glycans being eluted first. Coelution of permethylated glycans is observed for the more complex samples, but because of MS detection these overlapping glycan species can still be identified [43, 51, 52]. Ritamo et al [44] and Zhou et al [50] observed separation of isomers, although in some cases the sample complexity was limited.…”
Section: Separation Of Permethylated Glycansmentioning
confidence: 99%
“…From MS detection the different coeluted glycans could be identified. Isomers of glycans were also separatedESI-MS+[51]2016Alltech Adsorbosphere RP C 18 columnIsocratic methanol–water (80:20) containing 1 % acetic acidAcidicOligosaccharidesPermethylationRP chromatography was only used to separate glycans from salt contaminantsESI-MS+[121]1997Hypersil C 18 ; 100 mm × 2.1 mm (0.2–0.4 mL/min)Gradient and isocratic measurements with water and methanol and/or acetonitrile buffered with 1 mM sodium acetateAcidicPermethylated oligosaccharide mixtures2-Aminobenzamide and permethylationα and β anomers were differentiated in some cases, but in other measurements the separation of diantennary, triantennary and tetraantennary glycans was poorESI-MS+[122]2001Hypersil ODS C 18 3 μm; 150 mm × 4.6 mm (0.5–1.5 mL/min)Gradient of 50 mM formic acid in water adjusted to pH 5 with triethylamine and 50:50 first solvent–acetonitrile5.0 O -Glycans from bovine serum fetuin, human serum IgA1, human secretory IgA, human neutrophil gelatinase B, and human glycophorin A2-AminobenzamideLow peak capacity, glycan species were not separated individuallyFL (excitation 330 nm, emission 420 nm)An ion-pairing reagent (triethylamine) was added to separate glycans containing sialic acids.Glycans were analyzed in the low femtomole range[60]2002Hypersil ODS C 18 3 μm; 4.6 mm × 150 mm (0.5–1.5 mL/min)Gradient of 50 mM formic acid in water adjusted to pH 5 with triethylamine and 50:50 first solvent–acetonitrile5.0 N -Glycans and O -glycans from apolipoprotein (a)2-AminobenzamideGlycans were separated but the run time was 180 minFL (excitation 330 nm, emission 420 nm)[84]2001Acquity UPLC BEH C 18 1.7 μm; 100 mm × 2.1 mm (0.350 mL/min)Gradient of water and 25:75 methanol–water both containing 20 mM diethylamine (ion-pairing agent) and 50 mM formic acidAcidicReleased N -glycans from monoclonal antibodies, fetuin, and RNase B2-AminobenzamideSelectivity for glycans is low and low peak capacityFL (excitation 250 nm, emission 428 nm)An ion-pairing reagent (diethylamine) was added to separate glycans containing sialic acids[61]2011Nano-LC RP trap column: PepMap 100 3 μm; 300 μm × 5 mm.RP nano column: PepMap C 18 100 3 μm; 75 μm × 150 mm (gradient pump 150 nL/min and microflow pump 10 μL/min)Gradient pump: gradient of 0.4 % acetonitrile in water with 0.1 % formic acid and water–acetonitrile (5:95 v/v) contain...…”
Section: Introductionmentioning
confidence: 99%